Examining the effect of patient personality types and coping styles on outcomes of genetic counseling. Issue 1 (1st August 2022) - Salman, Areesha; Morris, Emily; Inglis, Angela; Austin, Jehannine
Abstract: Both empirical data and genetic counselors' clinical experience suggest that patients differ in the extent to which they benefit from genetic counseling (GC). Understanding the origins of these differences could help adapt services to ensure that all patients benefit fully, and potentially inform triage. Although patient personality dimensions and coping styles have been shown to influence outcomes of other psychological interventions, they have remained largely unexplored in relation to GC outcomes. We conducted an exploratory, descriptive study to assess relationships between patient personality dimensions, coping styles, and outcomes of GC. We recruited patients from a psychiatric genetics clinic who had – in the prior 7 years ‐ completed the GC Outcomes Scale (GCOS, a measure of empowerment) immediately prior to, and approximately one month after their appointment, and asked them to complete validated measures of personality and coping style. Interactions between each personality dimension or coping style and GCOS score were assessed using mixed‐effects linear regression models. Among the 169 participants, GCOS score increased by an average of 16.48 points ( SD = 12.59). Though extraversion, conscientiousness, neuroticism, and all three coping styles significantly predicted GCOS score ( p < 0.02), there was no relationship between these variables and time. For example, though a high score on conscientiousness predicted higher GCOS scores, it did not predict greater change in GCOS – people with higher scores on this dimension of personality had higher GCOS scores both pre‐ and post‐ GC. These preliminary data suggest that genetic counseling may increase empowerment regardless of personality dimensions and coping styles.